THz frequency generation using Gaussian pulse for medical applications - Afroozeh, A.; Innate, K.; Ali, J.; Yupapin, P. P. (My University, 2013)
We propose a new design of THz frequency carrier generation for medical applications. The dense wavelength division multiplexing can be generated by using a Gaussian pulse propagating within a modified PANDA ring resonator and add-drop filter. Results obtained have shown that broad region of frequency band can be obtained between 30 and 100 THz. This area of frequency band can be useful for medical applications, in which the broad bandwidth of THz signals can be obtained and available for medical applications, for instance, the use of Terahertz pulse imaging (TPI) and signal transduction therapy, especially, for blood vessel extraction are discussed. © 2012 Elsevier GmbH. All rights reserved.
Keywords: Biomedical optics; Medical optics; Signal transduction therapy; THz technology